2012
DOI: 10.1007/s00408-012-9389-5
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbations in Idiopathic Pulmonary Fibrosis Triggered by Pulmonary and Nonpulmonary Surgery: A Case Series and Comprehensive Review of the Literature

Abstract: Acute exacerbations of IPF can occur postoperatively after both pulmonary and nonpulmonary surgery and are associated with a high mortality rate. As a next step, a prospective multicenter clinical study of patients with IPF undergoing both pulmonary and nonpulmonary surgeries would allow the identification of perioperative risk factors in the development of AE of IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 26 publications
2
52
0
4
Order By: Relevance
“…For example, idiopathic AE-IPF is more common in the winter months [24,30], and in patients that are immunosuppressed [9], indicating that some cases of idiopathic AE-IPF may be triggered by a preceding infection [40][41][42]. Additional potential triggers that can lead to a similar presentation in patients with IPF include aspiration [43,44], pollution [45], thoracic surgical procedures [20,25,26,37,[46][47][48][49][50], cryobiopsy [51] and, possibly, bronchoalveolar lavage [20,52]. AE-IPF has also been reported following non-pulmonary surgery [47], potentially related to mechanical trauma secondary to mechanical ventilation.…”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, idiopathic AE-IPF is more common in the winter months [24,30], and in patients that are immunosuppressed [9], indicating that some cases of idiopathic AE-IPF may be triggered by a preceding infection [40][41][42]. Additional potential triggers that can lead to a similar presentation in patients with IPF include aspiration [43,44], pollution [45], thoracic surgical procedures [20,25,26,37,[46][47][48][49][50], cryobiopsy [51] and, possibly, bronchoalveolar lavage [20,52]. AE-IPF has also been reported following non-pulmonary surgery [47], potentially related to mechanical trauma secondary to mechanical ventilation.…”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%
“…Additional potential triggers that can lead to a similar presentation in patients with IPF include aspiration [43,44], pollution [45], thoracic surgical procedures [20,25,26,37,[46][47][48][49][50], cryobiopsy [51] and, possibly, bronchoalveolar lavage [20,52]. AE-IPF has also been reported following non-pulmonary surgery [47], potentially related to mechanical trauma secondary to mechanical ventilation. Acute lung injury similar to AE-IPF can also occur secondary to direct pulmonary toxicity from medications or thoracic radiation [53,54], particularly chemotherapy and immunosuppressive biological therapies.…”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%
“…LESLIE [31] argues that in these areas the traction forces and alveolar collapse are greatest, leading to sheer stress, lung injury and activation of fibrotic cascades. By analogy, mechanical ventilation in IPF can be a risk factor for acute exacerbations of the pulmonary fibrosis [32]. If pressure differences play a role in the pathogenesis of IPF, it could be speculated that the pressure differences caused by cough might influence disease behaviour itself.…”
Section: Pathophysiology Of Cough In Ipfmentioning
confidence: 99%
“…Such cases have severe dyspnea even at rest. Reduced forced vital capacity (FVC), non-smoker, and elevation of Krebs von den Lungen-6 (KL-6) have been reported as candidate risk factors for AE [15][16][17][18]. Recently, Arai et al [19] reported a diffuse HRCT pattern, lower serum IgG, and higher serum surfactant protein-D in AE diagnosis.…”
Section: Clinical Symptomsmentioning
confidence: 99%